2021
DOI: 10.1017/9781108966610
|View full text |Cite
|
Sign up to set email alerts
|

International Norms, Moral Psychology, and Neuroscience

Abstract: Research on international norms has yet to answer satisfactorily some of our own most important questions about the origins of norms and the conditions under which some norms win out over others. The authors argue that international relations (IR) theorists should engage more with research in moral psychology and neuroscience to advance theories of norm emergence and resonance. This Element first provides an overview of six areas of research in neuroscience and moral psychology that hold particular promise for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 126 publications
0
6
0
1
Order By: Relevance
“…Our study also contributes an important finding concerning the application of the MFT, a promising theoretical framework to study moral intuitions relevant to our field (Price and Sikkink 2021). Graham et al (2011) previously found that while the MFT has universal applicability, there are substantial cross-cultural variations across regions, particularly with respect to the differences between Western and non-Western countries.…”
Section: Discussionmentioning
confidence: 70%
“…Our study also contributes an important finding concerning the application of the MFT, a promising theoretical framework to study moral intuitions relevant to our field (Price and Sikkink 2021). Graham et al (2011) previously found that while the MFT has universal applicability, there are substantial cross-cultural variations across regions, particularly with respect to the differences between Western and non-Western countries.…”
Section: Discussionmentioning
confidence: 70%
“…Some may argue that all norms do ultimately depend on moral instincts or ideas. But baking morality into the definition is problematic, as norms can generate a sense of obligation without having an obvious moral component (see also Price and Sikkink, 2021: 4). The shared expectations about appropriate behavior that characterize norms can also have social, legal, or professional origins.…”
Section: Disaggregating Norms Morality and Principlesmentioning
confidence: 99%
“…Methodologically, this approach usually relies on surveys. We adapt it to interviews, answering Price and Sikkink’s (2021: 36) call for International Relations (IR) norms scholars to test “hypotheses generated in moral psychology using traditional political-science methods.”…”
Section: Introductionmentioning
confidence: 99%
“…In view of these developments, I complement scholarship on emotions and constructivist perspectives in particular and adopt a Bourdieusian approach to theorize the emergence of eco-grief. Constructivism advanced scholarship on emotions, but constructivists still grapple with the question of how emotions and norms emerge (Price and Sikkink, 2021). In their seminal article on norm entrepreneurs, Finnemore and Sikkink (1998) recognized emotions as a motivation for activism.…”
Section: Introductionmentioning
confidence: 99%
“…A turn to emotion entrepreneurs and emotional dynamics in transnational advocacy coalitions accords with developments in constructivism and implies extensions to available constructivist theories (Price and Sikkink, 2021). For example, during the development of the boomerang model, describing information sharing patterns among activists (Keck and Sikkink, 1998), constructivists analyzed scientific insights or normative frames but no emotional vocabularies.…”
Section: Introductionmentioning
confidence: 99%